Exposição de aves migratórias limícolas a metais pesados na costa maranhense, Brasil - SOUSA, Ana Paula Silva de (2016)
Whereas heavy metal contamination may be associated with population decline of migratory Nearctic shorebirds, this study found that the assimilation of these contaminants by Calidris pusilla and Arenaria interpres in two wintering areas on the north coast of Brazil, in the State of Maranhão, can contribute as a factor for the population decline of the species. Metals cadmium, lead, copper, chromium, mercury, selenium and zinc were analyzed in contour feathers of 15 individuals of each species by atomic absorption spectrophotometer. There was a significant difference only for mercury between the two species. The average concentration of metals were below the threshold considered toxic to birds. The fact that the contamination did not reach the threshold considered harmful to both migratory species in this study is an indication that in this region, the heavy metal contamination is not considered a potential factor in the decline of populations of migratory birds that overwinter in north coast of Brazil, specially in Maranhão. However, migratory birds use different areas on the north coast of Brazil along different migration routes, which makes it necessary to expand the area in future studies.